The language situation in Sweden: the relationship between the main language and the national minority languages - Heikkilä, Riina (Sens public, 2010)
This article is based on the presentation at the conference "Cultural Diversity, Multilingualism and Ethnic Minorities in Sweden" arranged by The French Institute the 2nd and 3rd of September. The aim of the article is to give a short presentation of the language situation in Sweden today and to make a presentation on the main language Swedish and the five national minority languages.